DETERMINATION OF RATIONAL REGIMES FOR GRINDING BARREL-SHAPED SURFACES OF ROLLERS ENSURING THEIR ROUGHNESS ON RA PARAMETER WITHIN LIMITS OF 0,16–0,32 MICROMETERS - G. P. Krivko; D. A. Cherey (Наука и техника)
The paper considers peculiarities that ensure minimum forming surface roughness (Ra = 0,2) of barrel-type rollers in the roller radial spherical bearings under conditions of an actual production process.